A Systematic Review of Metacognitive Beliefs in Chronic Medical Conditions - Lenzo, Vittorio; Sardella, Alberto; Martino, Gabriella; Quattropani, Maria C. (Frontiers in Psychology, 2020)
Background Psychological functioning plays an important role in medical conditions and impacts patients’ quality of life. Previously, many studies highlighted the association of metacognition to both the development and the maintenance of emotional disorders. Recently, several researchers pointed out the relevant role of dysfunctional metacognitive beliefs in the context of chronic diseases. Hence, dysfunctional metacognitive beliefs could be directly related to anxiety and depression, regardless of the medical condition’s expression. The aim of this systematic review was to summarize the available evidence regarding the association of metacognition with anxiety, depression, and perceived quality of life, in the context of medical conditions, according to Wells’ theory. Methods A systematic review based on electronic bibliographic databases (PsycINFO, PubMed, Scopus, Web of Science, and Web of Knowledge) of scientific literature was carried out. Studies involving patients evaluated in clinical settings were included in the analysis. Results Our findings indicated that metacognition appears to be related to anxiety, depression, and quality of life in patients with medical chronic conditions. Therefore, dysfunctional metacognitive beliefs might be a relevant factor associated with the process of adapting to illness. Conclusions The additional evaluation of metacognitive factors in the context of several medical chronic conditions appears valuable. Since the rising interest in the study of metacognition, suggestions for future research have been eventually provided.